Agri-environmental schemes and grassland biodiversity: Another side of the coin - Angela Münch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
In this paper part of the existing Agri-Environmental Schemes (AES) of the European Union are evaluated by using data on county level instead of applying field studies. The attempt is made to disentangle the effects of AES on land management practice as well as land use on biodiversity. It is argued that subsidies as AES should promote environmental-friendly land use which, in turn, should lead to biodiversity conservation. First results show that AES promotes ecological land use rather than extensive agricultural practice. Furthermore, AES is predominantly allocated in biodiversity rich counties and not in counties with low biodiversity which should be enhanced. Furthermore, no clear evidence is so far found, that land use practice is improving the biodiversity status.
Keywords: Q18; Q58; R14; 330; AES effectiveness; biodiversity; policy evaluation; EU-Agrarpolitik; EU-Umweltpolitik; Wirkungsanalyse; Landwirtschaft; Landschaftspflege; Biodiversität; EU-Staaten